A Secure Environment for Unsafe Component Loading (International Journal of Engineering and Computer Science, 2017)
Dynamic loading is widely used in designing and implementing software. Its benefits include modularity and generic interfaces for third-party software such as plug-ins. Dynamic loading components are utilization requires local file system access on the end host. The following problems are occurred in the local and remote dynamic components loading. In local system, the file does not exist in the specified Path or the specified search directories, hijacking the components. Although in the remote system, the browser automatically download arbitrary files to the user’s Desktop directory without any prompting, vulnerable program starts up via the shortcut, an archive file containing a document and a malicious component. In existing system the admin have to analyze the profile to check unsafe components. The proposed system has a facility to construct a profile for unsafe component by user.